Hype or hope? A new look at the research on cultural intelligence. (September 2018) - Fang, Fang; Schei, Vidar; Selart, Marcus
Abstract: Cultural intelligence (CQ), the capability by which expatriates, managers, and others involved in cross-cultural interactions function effectively in a globalized world, was introduced in 2002 and has garnered wide attention recently. In this paper, we present a detailed and up-to-date review of 142 empirical articles in the CQ research field. We first examine the concept of CQ, including its definition, structure, measurement, and validity. We then review the vast number of empirical studies that investigate the antecedents, development, direct and indirect effects, moderating effects, and aggregated effects of CQ, as well as qualitative studies. The analysis shows several issues that likely will be relevant to the research debate in the near future. These issues include investigations of (1) whether cultural intelligence is universal or culture-specific, (2) why objective measures that assess CQ are lacking, (3) to what extent a person can develop cultural intelligence, (4) to what extent there are dark sides to cultural intelligence, and (5) the role cultural intelligence plays as a predictor of individual and group performance. Addressing these questions may help us reveal the true potential of CQ in contemporary organizations and thus, affirm that the promise of CQ is more than just hype.